Gender Dynamics in Politics: A study of Latin America - Aparaajita Pandey (ASIAN Journal of International Peace & Security (AJIPS), 2021)
Latin America and the Caribbean went from a region at the top of the World’s Female Leader Index in 2014 to a region with no female heads of state in 2019. As the region displays a major shift towards the conservative side of politics, the gender, race, and class divide has never held more prominence in the politics of Latin America. The interaction between the gender, race, and class has meandered in interesting and unexpected ways; however, an overall diminishing the percentages of women in politics at the local, provincial, and central level has become apparent. Even after the implementation of special quotas for women, the numbers have steadily declined as the nature of politics in the region made a shift towards the right. As the politics of the region changes, women have also begun to make a mark among conservative leaders however; it is still unclear what their future would be. This article takes cues from the recent shift in Latin American politics to assess the nature of women participation and the conflict of gender in politics of the region and its larger impact on the society.